Oral Motor Intervention Improved the Oral Feeding in Preterm Infants. Issue 31 (August 2015) - Tian, Xu; Yi, Li-Juan; Zhang, Lei; Zhou, Jian-Guo; Ma, Li; Ou, Yang-Xiang; Shuai, Ting; Zeng, Zi; Song, Guo-Min; M. Jose, Carbonero Celis.
<x xml:space="preserve">Abstract</x> Abstract Oral feeding for preterm infants has been a thorny problem worldwide. To improve the efficacy of oral feeding in preterm infants, oral motor intervention (OMI), which consists of nonnutritive sucking, oral stimulation, and oral support, was developed. Published studies demonstrated that OMI may be as an alternative treatment to solve this problem; however, these results remain controversial. We conducted a meta-analysis with trial sequential analysis (TSA) to objectively evaluate the potential of OMI for improving the current status of oral feeding in preterm infants. A search of PubMed, EMBASE, Web of Science, the Cochrane Library, and China National Knowledge Infrastructure was performed to capture relevant citations until at the end of October, 2014. Lists of references of eligible studies and reviews were also hand-checked to include any latent studies. Two independent investigators screened literature, extracted data, and assessed the methodology, and then a meta-analysis and TSA was performed by using Reviewer Manager (RevMan) 5.3 and TSA 0.9 beta, respectively. A total of 11 randomized controlled trials (RCTs), which included 855 participants, were incorporated into our meta-analysis. The meta-analyses suggested that OMI is associated with the reduced transition time (ie, the time needed from tube feeding to totally oral feeding) (mean difference [MD], −4.03; 95% confidence interval [CI], −5.22 to −2.84), shorten hospital stays (MD, −3.64; 95% CI, −5.57 to −1.71), increased feeding efficiency (MD, 0.08; 95% CI, 0.36–1.27), and intake of milk (MD, 0.14; 95% CI, 0.06–0.21) rather than weight gain. Results of TSA for each outcomes of interest confirmed these pooled results. With present evidences, OMI can be as an alternative to improve the condition of transition time, length of hospital stays, feeding efficiency, and intake of milk in preterm infants. However, the pooled results may be impaired due to low quality included, and thus, well-designed and large RCTs were needed to further established effects.